Project-level Women’s Empowerment in Agriculture Index for Market Inclusion (pro-WEAI+MI) - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
It was validated using a combination of cognitive interviewing and qualitative and quantitative analysis based on pilot testing in Bangladesh, Philippines, Benin, and Malawi. A new Walmart Foundation funded project pilots it with additional indicators focused on marketable agricultural products and agriculture-based collectives in more countries.